GAMBARAN PERILAKU IBU DALAM PEMBERIAN ASI DAN MPASI PADA ANAK 0-2 TAHUN DI WILAYAH PUSKESMAS PEMBANTU PADANG BULAN KECAMATAN RANTAU UTARA KABUPATEN LABUHAN BATU 2017 - Bidari Armaya; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Behavior from a biological point of view is concerned organism activity that can be observed directly or indirectly. Mother is the name for the woman who gave birth to us, a woman who has been married, call prevalent in women. Breastfeeding is one of the components of the reproductive process consisting of menstruation, conception, pregnancy, childbirth, lactation, and weaning. Exclusive breastfeeding of infants aged 0-6 months is given only breast milk without giving additional food or other drinks. This research was conducted to see the description of mother's behavior in breastfeeding and food complementary in children 0-2 years in Area of ​​Puskesmas Pembantu Padang Bulan Subdistrict of North Rantau Labuhanbatu Regency 2017. This research is a descriptive research with cross sectional design. Data obtained from direct interviews to mother of toddler which include data of knowledge, attitude, and action of mother about breastfeeding and food complementary . Analysis of data processed and analyzed descriptively, presented in the form of frequency distribution table. The result of this research shows that knowledge on good category breast feeding is higher that is 52,5%, for giving exclusing breastfeeding is 46,3%,on food complementary of good category is higher that is 73,8%. Attitudes on breast feeding category is not good higher tht is 51.3%, in food complementary  category not good higher that is 52,5%. The action on breastfeeding category is not good is higher that is 55%, in food complementary  category not good higher that is 55,1%. Based on the results of the study is expected to increase counseling about breastfeeding and food complementary  are good to children under two and for health workers to motivate health cadres in disseminating information to mothers about breastfeeding and food complementary  are good against children under two. Keywords: Breastfeeding,Food Complementary, Mother’s Behavior, and children under-two.